Causes of late leaks in peritoneal dialysis patients - (:unkn) unknown (EDTNA-ERCA, 2002)
Background/Aims: Late dialysis leakage is an important complication of peritoneal dialysis. The aim of our study was to investigate the causes of late leaks in patients on peritoneal dialysis. Methods: 25 patients (19 F: 6 M; mean age: 56 ± 14) with and 25 patients (10 F: 15 M; mean age: 57 ± 12) without dialysis leakage on maintenance peritoneal dialysis treatment were included in the study. Data on demographic characteristics including age, sex, body mass index, body surface area, primary renal disease and peritoneal dialysis characteristics including implantation technique of the catheter, site of the catheter, time from catheter implantation to initiation of peritoneal dialysis, daily total filling volumes, use of hypertonic solutions, membrane transport properties and total and peritoneal creatinine clearances were retrospectively collected for both groups. Results: The number of female vs. male patients (76% vs. 40%, p < 0.05) and patients on CAPD vs. APD (68% vs. 56%, p < 0.05) were significantly higher in the group with dialysis leakage. Patients with leakage also had lower average transport properties (p < 0.05) and lower total creatinine clearances (p < 0.05). Other demographic and peritoneal dialysis characteristics were similar in both groups. Conclusions: Female gender and CAPD as opposed to male gender and APD are the risk factors involved in the development of late dialysis leaks. Peritoneal membrane transport characteristics as well as total creatinine clearance also seems to influence the development of complications.
Keywords: Complications; Leaks; Peritoneal dialysis; Retrospective study